PERAWATAN PULPOTOMI MORTAL SATU KALI KUNJUNGAN PADA MOLAR SULUNG NON VITAL (Laporan Kasus) - Bariah Bariah; Ismu Suharsono Suwelo (Faculty of Dentistry, Universitas Indonesia, 2015)
Non-vital teeth are supposed to be treated with root canal treatment and root canal filling. However, the problem on root canal treatment on deciduous molars, especially with children who is noncooperative because the difficulty to get access to the root canal on children and root canals on deciduous molars are very complex. Mortal pulpotomy is the way to eliminate necrotic pulp tissue in pulp chamber and replace it with material filling. The material is a combination between formocresol and zinc oxide eugenol. The result on formocresol pulpotomy on deciduous teeth can be seen in clinical, radiographic and histological examination of the teeth, abutment tissue and the growth permanent teeth germ. On this patient the mortal pulpotomy treatment had been done with formocresol on one visit. After a month, on the clinical evaluation there are no subjective complaints and no signs of gingival inflammation.